Internalizacja popkulturowych wzorców atrakcyjności fizycznej przez użytkowników mediów społecznościowych – konteksty społeczno-kulturowe i edukacyjne - Leksy, Karina (Pedagogika Społeczna Nova, 2024)
The article aims to present social media’s importance for internalizing the ideal body promoted in popular culture. Internalization of a culturally and socially desirable body image is associated with body image disorders, low self-esteem, and risky behaviors aimed mainly at reducing body weight among women and increasing musculature among men. The research presented in the article was conducted on 493 young adults via an online survey. In the group of women, the statistical analysis showed a correlation between the degree of agreement with the statement about the role of social media as a source of information about fashion and physical attractiveness and the preference for thinness. This result suggests the small body shape’s internalization by the surveyed women. It indicates the need for psychoeducational activities in the critical reception of media content and education in healthy attitudes towards one’s body.